Automatic water droplet splash photography: Design and analysis of an Arduino-controlled solenoid triggering device - Khamdi, Nur; Nasution, Henry; Mulyadi, Mulyadi (National Research and Innovation Agency, 2025)
Capturing transient water droplet splashes poses significant challenges due to their millisecond-scale corona formations, with manual methods achieving only 3 % success rates. This study developed an Arduino-based automated photography system that integrates a solenoid-driven droplet generator and optocoupler-triggered camera to address this limitation. The device calculates droplet impact timing using gravitational acceleration by synchronizing solenoid activation and camera triggering via an Arduino Nano. Experimental trials at a 50 cm droplet height demonstrated 100 % capture accuracy at 105 ms delays, outperforming manual methods (6 % success). Photographer evaluations rated splash aesthetics at 50 cm as optimal (9/10), emphasizing crown symmetry and height. The optocoupler-based system achieved sub-millisecond response times, surpassing electromechanical alternatives. By reducing memory waste from failed captures by 94 %, this approach enhances efficiency in high-speed macro photography. These results validate the system’s reliability for studying fluid dynamics and surface interactions, offering a scalable framework for automated imaging applications in scientific and artistic domains.